Pendampingan Peningkatan Produksi dan Promosi Panganan Tradisional Balung Kethek Desa Dayu Sebagai Khas Wisata Kampung Purba - Wahyu Tri Hastiningsih; Anditha Sari; Wachid Yahya (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Dayu Village Gondangrejo Karanganyar has a leading tourist attraction in the form of the Dayu cluster early human museum. In accordance with the research and dedication that has been done, that still needs a touch to support existing tourism, namely from a culinary point of view, this aims to boost tourist interest in visiting Dayu village. Based on the initial identification, there were 2 main problems with the typical culinary of Dayu Village, namely problems in the production and marketing fields. From the initial identification above, the community service implementation team focused on increasing production capacity by providing production support equipment, CHSE socialization, food sanitation hygiene, and create a variety of flavors. while the marketing sector is given solutions for making labels/brands on packages, sealers on packages to make them look neat and creating promotional content on social media such as Instagram. Through the assistance provided, partners can further increase product productivity and increase sales of Balung Kethek as a typical tourist food in the area of the Dayu cluster early human museum.